Hybrid Synthesizer Based On Phase-Lock Loop (Pll) Driven Direct Digital Synthesizer (Dds) - Idris, Mohd Ibtisyam (Universiti Sains Malaysia, 2017)
Throughout the years, the development of a frequency synthesizer has evolved from large and heavy benchtop models to the compact size handheld synthesizer and now in modular form. Due to the fast-growing technology in wireless telecommunication industries and high expenditure or budget allocation to improve the military and defense system, the frequency synthesizer has become one of the highest demand instruments in the market now. The research will focus on conventional Phase-Lock Loop (PLL) and latest technology of Direct Digital Synthesizer (DDS) and combine to become a hybrid PLL driven DDS synthesizer. This research was triggered since there was minimum work that has been covered and undetermined performances for such hybrid design. Furthermore, the problems faced for standalone synthesizers can be overcome through the hybrid system design. Phase noise, switching speed and spectral purity was the performance evaluated for the proposed setup and was compared with a standalone DDS synthesizer. Results shows the FCWS switching speed improved but there was degradation seen on phase noise and spectral purity particularly on the subharmonics and reference spurious. The harmonics and normal mode switching speed shows no difference between both systems. Although there was some performance degradation observed, the proposed setup performances are still under specifications for high performances applications and there are rooms for future improvement to be one of the best synthesizer designs that the market could offer.